Administrative empowerment and its impact on enhancing the performance and creativity of employees - a field study in the General Company for Iraqi Ports - Haifa Abdel Ghani Odeh (Iraqi Journal for Administrative Sciences, 2025)
This research aims to demonstrate the impact of Managerial Empowerment in enhancing of the Employees Performance and Innovation in General Company of Iraqi Ports in Basra, which the researcher hypothesized that, and she adopted theoretically on the sources of Arabic and foreign in the literature of modern management, and practical on the style of descriptive statistics through a form questionnaire. The research concluded the importance of Managerial Empowerment in the work of the company by raisingthe performance level of employees and their sense of job satisfaction and loyalty and their affiliation to the company as well as readiness to provide innovative approaches to work.The most important recommended by the study is to increase the focus on the applications’ of concept managerial empowerment in high level as one of the modern management techniques, which improves the performance of the organization in light of changing circumstances in the Iraqi environment.